25‐Hydroxycholesterol modulates tau‐mediated neurodegeneration and microglial chemotaxis and phagocytosis. (1st February 2022) - Long, Justin M; Tran, Ainsley; Serrano, Javier R.; Bao, Xin; Wang, Chao; Reznikov, Joseph; Cashikar, Anil G; Paul, Steven M.; Holtzman, David M.
Abstract: Background: Immune activation is an important component of Alzheimer disease (AD) pathology, with microglia playing a critical role in driving ApoE‐dependent tau‐mediated neurodegeneration. The oxysterol 25‐hydroxycholesterol (25‐HC) is an established potent regulator of peripheral innate immune response, though less is known regarding its role in CNS neuroimmune pathobiology. The enzyme that synthesizes 25‐HC, cholesterol 25‐hydroxylase (CH25H), is exclusively expressed by microglia in the CNS and is significantly upregulated in human AD brain and in transgenic AD mouse models. We have recently reported pro‐inflammatory effects of 25‐HC in ApoE4‐expressing mouse microglia, including increased microglial IL‐1β secretion and inflammasome activation. In this study we explored the role of 25‐HC in ApoE‐dependent tau‐mediated neurodegeneration. Method: PS19 tauopathy mice previously crossed with ApoE targeted replacement (TR) mice were subsequently crossed with CH25H KO mice. Hippocampal (HC), entorhinal and pyriform cortical (EC/PC) and ventricular volumes were measured at 9 months of age. In vitro primary cell cultures containing neurons, mixed glia or microglia were utilized to evaluate effects of 25‐HC or 7α, 25‐dihydroxycholesterol (7α, 25‐diHC), on neurotoxicity, microglial cytokine secretion, chemotaxis and phagocytic activity. Result: We found that in female tau mice expressing human ApoE4, genetic deletion of CH25H was protective (increased EC/PC volumes and reduced ventricular volumes). Similar trends were observed in male mice though these were not statistically significant. In a neuronal‐glial co‐culture model of ApoE4‐mediated neurotoxicity, 25‐HC protected against neurite loss and neuronal death at low concentrations but was potently neurotoxic at higher concentrations. In primary microglial cultures, 25‐HC modulated secretion of a number of chemokines and provoked a potent microglial chemotaxic response that was most robust in microglia derived from CH25H KO, ApoE4‐TR or ApoE4‐TR‐CH25H KO mice. 7α, 25‐diHC also stimulated chemotaxis but less robustly than 25‐HC. Assays testing the effect of 25‐HC and 7α, 25‐diHC on phagocytosis in microglia were also performed, and these data will be presented. Conclusion: 25‐HC appears to modulate tau‐mediated neurodegeneration in an ApoE‐dependent manner, especially in female mice, possibly through effects on critical microglial cellular functions. CH25H and 25‐HC may be viable therapeutic targets for AD‐related neuroimmune activation.